Antinociceptive Activity of Borreria verticillata: In vivo and In silico Studies - Silva, Rosa H. M.; Lima, Nathália de Fátima M.; Lopes, Alberto J. O.; Vasconcelos, Cleydlenne C.; Mesquita, José W. C. de; Mesquita, Ludmilla S. S. de; Lima, Fernando C. V. M.; Ribeiro, Maria N. de S.; Ramos, Ricardo M.; Cartágenes, Maria do Socorro de S.; Garcia, João B. S. (Frontiers in Pharmacology, 2017)
Borreria verticillata (L.) G. Mey. known vassourinha has antibacterial, antimalarial, hepatoprotective, antioxidative, analgesic and anti-inflammatory, however, its antinociceptive action requires further studies. Aim of the study evaluated the antinociceptive activity of B. verticillata hydroalcoholic extract (EHBv) and ethyl acetate fraction (FAc) by in vivo and in silico studies. In vivo assessment included the paw edema test, writhing test, formalin test and tail flick test. Wistar rats and Swiss mice were divided into 6 groups and given the following treatments oral: 0.9% NaCl control group (CTRL), 10 mg/kg memantine (MEM), 10 mg/kg indomethacin (INDO), 500 mg/kg EHBv (EHBv 500), 25 mg/kg FAc (FAc 25) and 50 mg/kg FAc (FAc 50). EHBv, FAc 25 and 50 treatments exhibited anti-edematous and peripheral antinociceptive effects. For in silico assessment, compounds identified in FAc were subjected to molecular docking with COX-2, GluN1a and GluN2B. Ursolic acid (UA) was the compound with best affinity parameters (binding energy and inhibition constant) for COX-2, GluN1a, GluN2B and was selected for further analysis with molecular dynamics (MD) simulations. In MD simulations, UA exhibited highly frequent interactions with residues Arg120 and Glu524 in the COX-2 active site and NMDA, whereby it might prevent COX-2 and NMDA receptor activation. Treatment with UA 10 mg/Kg showed peripheral and central antinociceptive effect. The antinociceptive effect of B. verticillata might be predominantly attributed to peripheral actions, including the participation of anti-inflammatory components. Ursolic acid is the main active component and seems to be a promising source of COX-2 inhibitors and NMDA receptor antagonists.